A critical-plane-based thermomechanical fatigue lifetime prediction model and its application in nickel-based single-crystal turbine blades. (4th July 2019) - Wang, Rongqiao; Zhang, Bin; Hu, Dianyin; Jiang, Kanghe; Mao, Jianxing; Jing, Fulei
ABSTRACT: In this study, thermomechanical fatigue (TMF) behaviours, failure mechanisms and the lifetime prediction method of a nickel-based single-crystal superalloy with [001] orientation were investigated based on the stress-controlled TMF experiments at different stress/temperature ranges, dwell times and phase angles. The fractographic observations revealed a creep-fatigue failure mechanism for in-phase thermomechanical fatigue (IP TMF) and an oxidation-fatigue failure mechanism for out-of-phase thermomechanical fatigue (OP TMF). According to the observed physical phenomenon of the slip along particular planes during the deformation process, selecting the steady-ratcheting shear-strain rate as the representative physical quantity, a new critical-plane-based lifetime prediction model which was suitable for a variety of experiment conditions was established. The predicted lifetimes for both standard specimens and turbine blades showed good agreements with the experimental data. The strong versatility and the concise mathematic form that made the model have some practical application value.